Isolation &Identification of Newcastle Disease Virus From Wild Pigeons: Anton Sabri AL-bana , Aida Bara Allawe , Ameen Ahmed Sebbar - AL-bana, Anton Sabri (The Iraqi Journal of Veterinary Medicine, 2020)
Isolation &identification of Newcastle disease virus from wild pigeonsinhabiting University of Baghdad (Al-Khwarizmi College of engineering)where velogenic and devastating infection of birds was encountered. Chickenembryos fibroblasts (CEF) were used for virus isolation (from infectedspleen and lungs) and propagation. Viral cytopathogenic effect was noticedon infected (CEF) cell culture within (24) hr post inoculation. The virus wasidentified by heamagglutination inhibition (HI) test using reference antiNDV serum.